VIBRIO SP. ATTACK ON DOMESTICATED MANTIS SHRIMP, HARPIOSQUILLA RAPHIDEA - Yusli Wardiatno (Buletin PSP, 2012)
The mantis shrimp, Harpiosquilla raphidea, is an economically valued crustacean species caught mainly in some Indonesian coastal waters, and is the main target of fisherman in Kuala Tungkal, Province Jambi. To avoid the extinction of the species due to intensive exploitation, a domestication effort was conducted in laboratory. The domestication was aimed to observe gonad development in female shrimp. However, during domestication necrosis and some clinical signs of vibriosis occurred. Microbial isolation from  hepatopancreas, intestine, gills and uropod of infected shrimps found Vibrio sp. The occurrence of vibriosis seems to affect gonad development in females. Besides, the Vibrio sp. attack caused total mortality also.    Key words: vibrio, vibriosis, mantis shrimp, gonadal development